ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI SUMATERA SELATAN - Nita Darma Sari (Jurnal Ekonomi Pembangunan, 2005)
This research is aimed to describe some variables influence the Vehicle Tax  Revenues.  Analysis used in this research was Quantitative analysis and formulated in a Quadratic Regression Model.  The output shows that variables influence vehicle tax revenues were per capita income, vehicles sums, vehicles tax tariff and inflation simultaneously significant to Vehicle Tax Revenues in coefficient correlation = 0,999  (99,9%).  The output regression  was positive and significant to vehicles sums and vehicles tax tariff, whereas per capita income and  inflation were insignificant as statistic. Keywords: vehicle sums, vehicle tax tariff, inflation.